Relationship between Soil-Transmitted Helminth and Anemia in Elementary School Students Negeri 96 and 97 Palembang - Indri Ramayanti; Atika Safitri Armo; Miranti Dwi Hartanti; Ahmad Ghiffari (Britain International of Exact Sciences (BIoEx) Journal, 2021)
Soil-transmitted helminth (STH) prevalence is high worldwide. School-aged children are at risk of infection due to poor self-hygiene and contaminated soil and water. Anemia is caused by infection in children, and it affects cognitive development, physical development, and school performance. To ascertain the relationship and distribution of STH and anemia in elementary school students, as the cross-sectional objectives. Students from SDN 96 and 97 Palembang participated in the study. Using stratified random sampling, 84 students from grades 4, 5, and 6 were chosen at random. Anemia is diagnosed through a test using the Quick Check hemoglobin method. They discovered that 40.5 percent of students had intestinal worms, 15.5 percent were anemic, and 11.8 percent were both anemic and worm-infected. A p-value of 0.438 was obtained from the chi-square bivariate analysis. There is no link between STH and anemia.